Analyzing the Web-Based Library Information System at SMKN 1 Talang Ubi - Marlindawati, .; Misinem, .; Muhammad, Ardiyansyah (INTI International University, 2024)
In the rapidly evolving field of information technology, the transition from manual to computerized systems has become essential for improving efficiency and accessibility. This study focuses on the analysis, development,and evaluation of a Web-Based Library Information System at SMK Negeri 1 Talang Ubi, aimed at modernizing library management through automation. The system facilitates processes such as book borrowing, member registration, and data management, with the added benefit of remote accessibility. The system was developed using the Web Engineering methodology, which includes stages of Customer Communication, Planning, Modeling, Construction, and Delivery & Feedback. UML (Unified Modeling Language) tools were employed for system design, and PHP, HTML, and MySQL were utilized for programming and database management. Usability testing with 100 participants revealed positive outcomes: 80% rated the system's navigation and design as "Excellent" or "Good," and 80% found the user interface consistent across different sections. However, 10% of participants experienced issues with device accessibility, indicating a need for further improvements in cross-device compatibility. Overall, 80% of users were satisfied with their experience. The Web-Based Library Information System at SMK Negeri 1 Talang Ubi has successfully enhanced library management through improved efficiency and accessibility. The high satisfaction rates among users highlight the system's strengths, although addressing cross-device accessibilityissues remains a priority. This study provides a valuable framework for other educational institutions seeking to implement similar web-based solutions